فاعلية برنامج قائم على السبك النحوي في تطبيق عمل كان وأخواتها والضبط الإعرابي الخاص بها لطلاب الصف الأول الثانوي - عبده، أحمد عبده عوض; عرفة، إيمان السيد; جاويش، الشيماء عبدالمنعم عبدالله (جامعة كفر الشيخ - كلية التربية, 2023)
استهدف البحث الحالي التعرف على فاعلية برنامج قائم على السبك النحوي في تطبيق عمل كان وأخواتها والضبط الإعرابي الخاص بها لطلاب الصف الأول الثانوي، وفي سبيل هذا الهدف استخدم هذا البحث المنهج الوصفي والمنهج شبه التجريبي وأعدت الباحثة الأدوات التالية والتي تمثلت في: ۱- اختبار تحصيلي للطلاب لمعرفة مدى إلمام طلاب الصف الأول الثانوي بتطبيق عمل كان وأخواتها، حيث طبق الاختبار قبليًا وبعديًا. ۲- اختبار تحصيلي للطلاب لمعرفة مدى إلمام طلاب الصف الأول الثانوي بمهارات الضبط الإعرابي الخاص بكان وأخواتها، حيث طبق الاختبار قبليًا وبعديًا . 3- البرنامج القائم على السبك النحوي في تطبيق عمل كان وأخواتها والضبط الإعرابي الخاص بها لطلاب الصف الأول الثانوي. وبعد تطبيق البرنامج يمكن إيجاز أهم النتائج فيما يلي: 1- توصل هذا البحث إلى ضعف طلاب الصف الأول الثانوي في تطبيق عمل كان وأخواتها والضبط الإعرابي الخاص بها. ٢- توصل هذا البحث إلى فاعلية البرنامج القائم على السبك النحوي في تطبيق عمل كان وأخواتها والضبط الإعرابي الخاص بها لطلاب الصف الأول الثانوي. The current research aimed to identify the effectiveness of a program based on grammatical casting in the application of the function of Kiana and its equivalents and their grammatical control for first-year secondary school students, for this purpose, this research used the descriptive approach and the semi-experimental approach, the researcher prepared the following tools, which consisted of: 1- A cognitive achievement test for students to find out the extent to which first year secondary students are familiar with applying the work of Kiana and its equivalents, Where the test was applied before and after. 2- A cognitive achievement test for students to find out the extent to which first year secondary students are familiar with applying the skill of the grammatical control of Kiana and its equivalents, Where the test was applied before and after. 3- A program based on grammatical casting in the application of the function of Kiana and its equivalents and their grammatical control for first-year secondary school students. After applying the program, the most important results can be presented as follows: 1- This research found the weakness of first year secondary students in applying the work of Kiana and its equivalents and their grammatical control. 2- This research reached the effectiveness of a program based on Grammatical casting in the application of the function of Kiana and its equivalent and their grammatical control for first-year secondary school students.
Keywords: اللغة العربية -- النحو العربي -- التراكيب الصرفية -- الضبط الإعرابي